Unusual optical observations of OI greenline during a geospace event on 1 February 2008 - Narayanan, V. Lakshmi; Gurubaran, S.; Emperumal, K.; Patil, P.T. (My University, 2011)
We herein report the first observations of an unusual phenomenon recorded by an all‐sky airglow imager from the low‐latitude site Panhala (16.8°N, 74.1°E, geographic; 8.2°N geomagnetic), on the night of 1 February 2008, during the main phase of a moderate geomagnetic storm. The observations of OI 557.7 nm emission reveal discrete, transient, filamentary structures referred to as “streaks.” No such features were seen in the OI 630.0 nm emission and the mesospheric sodium and hydroxyl emissions. Here we speculate on possible mechanisms for generation of such structures, though we cannot conclude firmly that any one of them was responsible for the observed features. This is a puzzling observation made from very low geomagnetic latitude during the main phase of a moderate recurrent geomagnetic storm in the declining phase of solar cycle. In spite of the limitations in identifying the mechanism or mechanisms responsible for this striking observation, it is felt that understanding of processes driving such unusual and rare events will substantiate our knowledge on the mysterious coupling processes occurring in the equatorial upper atmosphere.
Keywords: Optical observation; OI greenline; Geospace event; All-sky image; Low latitude; Panhala; Geomagnetic storm